Adenomyomectomy with preconceptional transabdominal cervicoisthmic cerclage for transvaginal cerclage failure - Kyong-No Lee; So-Yoon Park; Ga-Hyun Son; Ga-Hyun Son; Keun-Young Lee (Frontiers in Surgery)
BackgroundDespite evidence of adverse pregnancy outcomes associated with adenomyosis, there are no established strategies for risk assessment, stratification, or prevention of these potential complications. This study aimed to describe and evaluate the technique of adenomyomectomy with preconceptional transabdominal cervicoisthmic cerclage (TCIC) in high-risk women with an unfavorable history of previous preterm birth and/or second trimester miscarriage after transvaginal cerclage.MethodsEligible patients had adenomyosis, confirmed by ultrasound or biopsy, and a history of second trimester miscarriages or preterm deliveries before 28 weeks despite transvaginal cerclage. All patients underwent adenomyomectomy followed by preconceptional placement of TCIC. Their obstetric and gynecologic histories, surgical outcomes, and pregnancy courses were retrospectively reviewed. Of the 85 patients who underwent this procedure at our facility over a 10-year period, we report the outcomes of 17 patients with antenatal care and delivery records available at our hospital.ResultsSeventeen patients were included in the final analysis. Only one patient delivered before 34 weeks, and six between 34 and 37 weeks. One patient had three successful pregnancies following the procedure.ConclusionsAdenomyomectomy with preconceptional TCIC may be a viable treatment option for patients with adenomyosis who wish to have a successful pregnancy after a previous preterm delivery or miscarriage.